NAnnotated checklist of the tribe Listroderini (Coleoptera: Curculionidae: Cyclominae) - Morrone, Juan J. (Zootaxa, 2011)
The weevil tribe Listroderini (Curculionidae: Cyclominae) was originally recognized for a group of New World taxa. During the last decades its concept was expanded, and additional new taxa were described from the Americas, Australia, New Zealand, and the Tristan da Cunha-Gough islands. This checklist evaluates the nomenclatural status of all the generic and specific names applied to listroderines. A total of 407 species classified into 36 genera are recognized. The following synonymies are established: Gromilus insularis robustus Brookes, 1951 and G. insularis antipodarum Kuschel, 1964 = G. insularis Blanchard, 1853; Gromilus veneris setarius Broun, 1909 = G. veneris (Kirsch, 1877); and Listronotus oregonensis tessellatus Casey, 1895 = L. oregonensis (LeConte, 1876). Two secondary homonyms were detected and replacement names are proposed: Gromilus brounii for G. setosus (Broun, 1917 non Broun, 1893), and Gromilus kuschelii for G. striatus (Broun, 1921 non Broun, 1915).